2015
DOI: 10.15829/1560-4071-2014-10-73-76
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Markers in Hypertensive Disease in Siberian Population

Abstract: Цель. Проверить однонуклеотидные полиморфизмы (ОНП), идентифици-рованные в недавних ассоциативных исследованиях на пригодность в каче-стве маркёров риска развития артериальной гипертензии (АГ) в сибирской популяции. Материал и методы. Группа больных АГ и контрольная группа (отношение 2:1) были сформированы на основе популяционной выборки 45-69 летних жителей г. Новосибирска (9400 человек), которая была собрана в ходе работы по международному проекту HAPIEE. В исследование включены 514 человек, из них конт роль… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…(11)(12)(13)(14)(15)(16) The Russian study, which included 514 patients, found an association of the G allele with the risk for developing hypertension in men, with an odds ratio of 1.95 (P=0.003). (17) However, a number of studies did not find a reliable association of AG and GG genotypes with AH. (18)(19)(20)(21)(22) In Group 1 patients with AH, the average level of SBP in carriers of AA, AG and GG genotypes was 159.72±1.92 mmHg, 161.72±1.40 mmHg and 173.53±3.62 mmHg, respectively (F=6.6763, P=0.0016).…”
Section: Genotypementioning
confidence: 99%
“…(11)(12)(13)(14)(15)(16) The Russian study, which included 514 patients, found an association of the G allele with the risk for developing hypertension in men, with an odds ratio of 1.95 (P=0.003). (17) However, a number of studies did not find a reliable association of AG and GG genotypes with AH. (18)(19)(20)(21)(22) In Group 1 patients with AH, the average level of SBP in carriers of AA, AG and GG genotypes was 159.72±1.92 mmHg, 161.72±1.40 mmHg and 173.53±3.62 mmHg, respectively (F=6.6763, P=0.0016).…”
Section: Genotypementioning
confidence: 99%
“…Настоящая работа является второй частью публикации результатов исследования [10] и включает анализ по 8 маркерам.…”
Section: The Association Of Blood Pressure and Hypertension With Geneunclassified